Analysis of Regional Carbon Emission Decoupling Coupling in China Based on ArcGIS Analysis-Empirical Evidence From Urban-Rural Integration in Fujian Province - Xie, Renshan; Yu, Dongye; Zhang, Xingyuan; Yang, Ze; Yang, Jianzhou; Ye, Jie (Frontiers in Energy Research, 2022)
China’s ambitious measures for developing a low-carbon economy led to the “double carbon” target initiation. Under this national goal, reaching peak carbon emissions by 2030 is desired. This should not come at the cost of economic growth; which means carbon emissions can be reduced while economic growth can be achieved simultaneously. To realise this strategic reform, the first pilot ecological civilisation zone in Fujian Province of China was initiated; its outcome is set to be the responsible case for such initiations aiming at increased low-carbon economy development. Therefore, it is essential to investigate the relationship between carbon emissions and economic growth based on the evidence. Hence, we applied a model that combines the Tapio and Coupled coordination. Combining the Tapio and the coupled coordination models allows us to analyse carbon emissions and economic growth in Fujian Province over 20 years, i.e., 2001–2020. First, we divided the urban-rural integration process into four stages following China’s Five-Year Plan (FYP): T1 (2001–2005), T2 (2006–2010), T3 (2011–2015), and T4 (2016–2020). Second, ArcGIS mapping was used to represent the spatial evolution pattern of low-carbon economic development in Fujian Province. We observed that the low-carbon economy in Fujian Province had reached a point where the economic growth rate has already exceeded its carbon emission growth rate and is currently in a weak decoupling state. In addition, there observed a bifurcation pattern between carbon emissions and economic growth, especially in the coastal cities that are out of balance, whereas the inland cities are being coordinated. Overall, it is observed that the concept of ecological civilisation is crucial for China to achieve the “double carbon goal,” and it is high time to create accelerating measures that guide the integration of urban and rural areas in the future with appropriate infrastructure.